2000
DOI: 10.1159/000064849
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Ureteral Stone Management in 1,082 Patients Using Semirigid Ureteroscopes

Abstract: Objectives: To assess the efficacy and complications of ureteroscopic lithotripsy (URS) using semirigid ureteroscopes. Methods: We retrospectively analyzed the records of 1,082 consecutive patients with ureteral stones who were treated with URS with or without auxiliary extracorporeal shock wave lithotripsy for stone fragments. The efficacy was estimated using the stone-free rate and efficiency quotient (EQ). Results: The stone-free rates were 79.0, 90.4 and 93.2% for upper, middle and lower ureteral stones, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
6
0
2
Order By: Relevance
“…23,24 Most of these complications can be managed conservatively except avulsion. Mucosal injury observed in different studies range from 3.5-5%, 18,24 and mucosal injury in our study was seen in 2 (1.8%) patients. Some studies declared procedural failure or repeat procedure in range of 3-13%.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…23,24 Most of these complications can be managed conservatively except avulsion. Mucosal injury observed in different studies range from 3.5-5%, 18,24 and mucosal injury in our study was seen in 2 (1.8%) patients. Some studies declared procedural failure or repeat procedure in range of 3-13%.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, some authors recommend using baskets or graspers to remove larger fragments produced by the pneumatic lithotripter to reduce complications and also reduce the second procedure. [17][18][19] As we also used stone forceps in most of the procedures the second procedure was not performed except in only few of our patients. However, use of stone forceps caused mucosal injury in two patients (1.8%) that was treated with DJ stenting for 3weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, the semirigid ureteroscope has various success and complication rates in different segments of the ureter. Some authors emphasized a lower degree of success and high complication rates in the proximal ureter [14][15][16][17] . They also reported that the proximal ureter was one of the factors which cause unfavorable results when using the semirigid ureteroscope.…”
Section: Discussionmentioning
confidence: 99%
“…The reported overall stone-free rate of semirigid URS for ureteral stones is remarkably high at 85-100% depending on stone location [2,4,5]. The initial stone free rate independent of location was 85% in our patients; this rate increased to 98% after ancillary procedures.…”
Section: Discussionmentioning
confidence: 53%